THE EFFECT OF CREDIT RISK AND CAPITAL ADEQUACY ON PROFITABILITY WITH LIQUIDITY RISK AS A MEDIATION VARIABLE AT BANK WOORI SAUDARA - W. Katili, Sitti Nadiah; Ali, Muhammad; Fauzi R. Rahim (Journal of Business Issues, 2023)
This study aims to analyze the effect of credit risk and capital adequacy on profitability with liquidity risk as a mediating variable at Bank Woori Saudara. This study takes from the annual financial report at Bank Woori Saudara. To carry out the objectives of this study, an analysis technique using path analysis is used. The results of the analysis prove that the effect of credit risk on liquidity risk is significant with a negative relationship direction at Bank Woori Saudara. Capital adequacy Ratio does not have a significant effect on credit risk at Bank Woori Saudara. Credit risk, capital adequacy and liquidity risk do not have a significant effect on profitability at Bank Woori Saudara. While the mediating effect of liquidity risk is unable to mediate the relationship between credit risk and capital adequacy on profitability.